The Connor-Davidson Resilience Scale (CD-RISC): Dimensionality and age-related measurement invariance with Australian cricketers - Gucciardi, Daniel; Jackson, B.; Coulter, T.; Mallett, C. (2011)
Objective: This study explored the dimensionality and measurement invariance of the 25-item Connor-Davidson Resilience Scale (CD-RISC; Connor & Davidson, 2003) across samples of adult (n = 321; aged 20-36) and adolescent (n = 199; aged 12-18) Australian cricketers. Design: Cross-sectional, self-report survey. Methods: An online, multi-section questionnaire. Results: Confirmatory factor and item level analyses supported the psychometric superiority of a revised 10-item, unidimensional model of resilience over the original 25-item, five-factor measurement model. Positive and moderate correlations with hardiness as well as negative and moderate correlations with burnout components were evidenced thereby providing support for the convergent validity of the unidimensional model. Measurement invariance analyses of the unidimensional model across the two age-group samples supported configural (i.e., same factor structure across groups), metric (i.e., same pattern of factor loadings across the groups), and partial scalar invariance (i.e., mostly the same intercepts across the groups). Conclusion: Evidence for a psychometrically sound measure of resilient qualities of the individual provides an important foundation upon which researchers can identify the antecedents to and outcomes of resilience in sport contexts. © 2011 Elsevier Ltd.